The Portrayal of African Woman’s Struggle Reflected in the Novel “How Beautiful We Were” By Imbolo Mbue (2021) - Syahruni Junaid; Nahdhiyah Nahdhiyah; Dahlan Dahlan; Citra Andini; Azis Muh. Dzulhijjah (Hasanuddin University, 2024)
Ecofeminism is an understanding of the relationship between women and the universe that approaches issues of environmental degradation and social injustice from the premise that how we treat nature and how we treat each other are inseparable. This research discusses the character of a woman in the novel How Beautiful We Were which aims to find out the depiction of the struggle of African women in protecting their environment. This research uses the theory of ecofeminism from Greta Gaard and Murphy with descriptive qualitative research methods and note- taking as an instrument. This research was conducted to add and give awareness to readers about the importance of preserving and protecting the environment around us. The results found in this novel that the female character named Thula fulfills the three aspects of women's struggle in the theory of ecofeminism. The researcher concluded that in this novel, the most visible struggle of women leads to the community, so that the movement carried out by the main character is able to realize that it is important to fight for and protect our nature from the threat of companies that come to destroy it